Dynamics of the high-current ion beam in a section of the linear induction accelerator - Karas, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2015)
The dynamics of the high-current ion beam (HCIB) in a section of the linear induction accelerator (LIA), consisting of magneto-isolated accelerating gap and the two drift spaces, is studied. In the most suitable variant of the HCIB compensation by accompanying and colliding beams of electrons, the current of the ion beam at the exit of first drift gap is close to the original.The optimization of the system parameters (the value of magnetic field produced by the coils with opposing currents, the size of the system, the parameters of the beams) at which a uniform the length of the gap acceleration of the HCIB is achieved, has been carried out. Wherein the quality of the ion beam at the exit of the LIA section is kept acceptable for heavy-ion inertial fusion. Досліджена динаміка сильнострумового іонного пучка (СІП) в секції лінійного індукційного прискорювача (ЛІП), що складається із магнітоізольованого прискорюючого зазору та двох дрейфових проміжків. В більш прийнятному варіанті компенсації СІП супроводжуючим і зустрічним пучками електронів, струм іонного пучка на виході із першого дрейфового проміжку близький до початкового. Проведена оптимізація параметрів системи (величина магнітного поля, яке створено котушками із зустрічними струмами, розміри системи, параметри пучків), при яких досягається рівномірне прискорення СІП по довжині зазору. При цьому якість іонного пучка на виході із секції ЛІП зберігається прийнятною для інерційного термоядерного си-нтезу на важких іонах. Исследована динамика сильноточного ионного пучка (СИП) в секции линейного индукционного ускорителя (ЛИУ), состоящей из магнитоизолированного ускоряющего зазора и двух дрейфовых промежутков. В наиболее приемлемом варианте компенсации СИП сопровождающим и встречным пучками электронов, ток ионного пучка на выходе из первого дрейфового промежутка близок к первоначальному току. Проведена оптимизация параметров системы (величина магнитного поля, созданного катушками со встречными токами, размеры системы, параметры пучков), при которых достигается равномерное ускорение СИП по длине зазора. При этом качество ионного пучка на выходе из секции ЛИУ сохраняется приемлемым для инерциального термоядерного синтеза на тяжелых ионах.